Peer Support for Carers: A Qualitative Investigation of the Experiences of Carers and Peer Volunteers. (September 2013) - Greenwood, Nan; Habibi, Ruth; Mackenzie, Ann; Drennan, Vari; Easton, Nicky
Being a carer of someone with dementia can be rewarding and also challenging. Volunteer peer support schemes for carers are being introduced, little is known about either their impact on carers and volunteers or about volunteers' and carers' experiences. This study investigated peer volunteer and carer recipient experiences of a peer support service. Thematic analysis of 13 in-depth interviews with 9 carers and 4 peer volunteers revealed that peer support helped both carers and peer volunteers through the realization that they were "not alone" in their experiences and emotions. Additional carer benefits included opportunities to talk freely about difficult experiences and learning how others cope. Volunteers found their role rewarding, describing satisfaction from putting their own experiences to good use. These findings highlight the isolation and exclusion experienced by current and former carers of people with dementia and draw attention to the benefits of peer support for both the groups.